Role of Betahistine in the Management of Vertigo - Biswas, Anirban; Dutta, Nilotpal (Annals of Otology and Neurotology, 2018)
Though betahistine is the most commonly prescribed drug for vertigo, there are a lot of controversies on its efficacy as well as its proclaimed mechanism of action. There are authentic studies that have shown it to be no different from a placebo in Ménière’s disease. It is often promoted as a vestibular stimulant, but scientific evidence suggests that it is a vestibular suppressant. It is also not very clear whether it is an H3-receptor antagonist as most promotional literature shows it to be, or whether it is an inverse agonist of the H3 receptors. Owing to insufficient data on its efficacy in Ménière’s disease, betahistine is not approved by the U.S. Food and Drug Administration (FDA). The much-advertised role of betahistine in augmenting histaminergic transmission and thereby inducing arousal, though beneficial is some ways in the restoration of balance after peripheral vestibulopathy, is yet not without systemic problems, and the pros and cons of histaminergic stimulation in the brain need to be assessed more by clinical studies in humans before imbibing it in clinical practice. The effect of increasing blood flow to the cochlea and the vestibular labyrinth and “rebalancing the vestibular nuclei” (as claimed in some literature) and whether they are actually beneficial to the patient with vertigo in the therapeutic doses are very controversial issues. The mechanism of action of betahistine in vertigo in general and in Ménière’s disease in particular is very confusing, and there are too many conjectural and hypothetical, if not controversial issues involved that call for close scrutiny. Everything taken together, betahistine appears to be an unduly hyped-up drug and clinicians need to review the scientific literature available and be convinced about its efficacy and mechanism of action before using it in clinical practice. This review article puts forth some controversial issues and reviews the relevant scientific literature for clinicians to analyze and then take the final call on its clinical use.
Keywords: betahistine; treatment of vertigo; H3-receptor; treatment of Ménière’s disease; betahistine in Ménière’s disease